Representasi Makna Keikhlasan Pada Series “ Layangan Putus ” - Aisyah, Yola Hayatul; SM, Anis Endang; Maryaningsih, Maryaningsih (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This research was conducted to analyze the representation of sincerity shown by women in the drama series "Layangan Putus." In addition to being a form of mass media that portrays the social life of the community, this series also includes cultural creations that bring important values to the audience, one of which is about marital life rumored with infidelity and how women, especially wives, demonstrate an attitude of sincerity. This study used a qualitative descriptive approach with the analysis of Roland Barthes' semiotics model. The focus of this research was to find the denotative, connotative, and myth meanings in 4 scenes that show the meaning of sincerity. The data collection techniques used were documentation, literature review, and observation. The results of the study show that the meaning of sincerity is demonstrated as an action that refers to social situations, parties harmed in the social structure take action against those who harm them. The attitude of sincerity occurs because of human behaviors that are not in line with their true feelings and conditions and harm others, including family, by surrendering what is considered best in the hope of getting something more deserving in the future. Sincerity is an attitude that women adopt to prove that not all problems need to be responded to and vented through emotions, but in this series, it highlights the sense of sincerity that has already occurred in her married life.